DAMPAK PEMAKAIAN LENSA KONTAK LUNAK YANG TIDAK SESUAI STANDAR BAGI KESEHATAN MATA PASIEN REMAJA DI ACEH OPTICAL BANDA ACEH - Febry Corina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Impacts of Using Non-Compliant Soft Contact Lenses for the Eye Health of Adolescent Patients in Aceh Optical Banda Aceh. This study aims to determine the effects caused by soft contact lenses that are not by the standards for eye health in adolescent patients, the results of the study proved that respondents felt the result of wearing soft contact lenses that are not standard. This is evident from the several points raised cumulatively, it can be illustrated that the majority of respondents numbering 19 people (53.3%) have inadequate understanding of contact lenses and procedures for their use. Only 14 respondents (46.7%) were stated to have good knowledge and truly understood information about using soft contact lenses. The majority of adolescent patients (66.7%) in Aceh Optical Banda Aceh paid little attention to the procedure of using contact lenses, 18 respondents (60%) felt bad due to the use of soft contact lenses that were not up to standard and 12 respondents (40%) did not feel the result of wearing contact lenses software that is not standard.